Correlation with renin-angiotensin-aldosterone and glomerular filtration rate in chronic renal failure patients - Fatimah Kadhim Ibrahim AL-Mahdawi; Mazin Razooqi Mohammed; Mustafa Gheni Taher; Wasan A.Wahab Alsiadi; Ammar Kadi; Irina Potoroko; Marouane Chemek (Diyala Journal of Medicine, 2023)
Background: One of the more significant hormonal systems, the renin-angiotensin-aldosterone system, controls the kidney function, adrenal gland through its effect on the balance of sodium and potassium, blood pressure, fluid volume, and also manages the functions of cardiovascular.